Why surgical decompression of the carpal tunnel may not be effective. Obvious and unusual reasons for the failure of surgical treatment - M. R. Kalashnikova; A. K. Dulaev; D. G. Nakonechny; D. I. Kutianov; A. V. Zhigalo; V. V. Pochtenko; V. V. Morozov; E. V. Ogorodnik (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The objective was to analyze the possible reasons for the failure of surgical treatment of carpal tunnel syndrome.One of the most common forms of compression mononeuropathy of the upper extremity is carpal tunnel syndrome. Despite being widely studied, the topic remains relevant due to the fact that this pathology makes up the majority of occupational diseases and its treatment is associated with significant healthcare costs. Carpal tunnell release is the «gold standard» for surgical treatment of carpal tunnel syndrome, but despite its high level of effectiveness, from 2 to 10 % of patients require revision surgery for recurrent carpal tunnel syndrome.